2013
DOI: 10.1039/c2dt31575k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, magnetic properties and biological activity of supramolecular copper(ii) and nickel(ii) complexes with a Schiff base ligand derived from vitamin B6

Abstract: Three new complexes of Cu(II) and Ni(II), [Cu(II)(H(2)pydmedpt)](2+)·2Cl(-) (1), [Ni(II)(H(2)pydmedpt)](2+)·2Cl(-) (2) and [Ni(II)(pydmedpt)(OH)](-)·K(+) (3) of the Schiff base ligand [H(2)pydmedpt](2+)·2Cl(-) were synthesized by the in situ reaction of pyridoxal (pyd), a vitamer of vitamin B(6), N,N-bis[3-aminopropyl]methylamine (medpt) and copper(II) acetate or nickel(II) acetate, respectively. The molecular structures of 1 and 2 were determined by single crystal X-ray diffraction studies. The structure of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Copper (II) and nickel (II) complexes are regarded as the most of promising anti-carcinogen to replace the cisplatin, an idea supported by a considerable number of research articles describing the synthesis, DNA binding, and cytotoxic activities of numerous copper (II) complexes [12][13][14][15][16][17]. Certainly, a wide variety of polydentate organic ligands play a pivotal role to determine the properties of complexes [18].…”
Section: Introductionmentioning
confidence: 99%
“…Copper (II) and nickel (II) complexes are regarded as the most of promising anti-carcinogen to replace the cisplatin, an idea supported by a considerable number of research articles describing the synthesis, DNA binding, and cytotoxic activities of numerous copper (II) complexes [12][13][14][15][16][17]. Certainly, a wide variety of polydentate organic ligands play a pivotal role to determine the properties of complexes [18].…”
Section: Introductionmentioning
confidence: 99%
“…The compounds prepared are slightly to moderately soluble in water and the order of stability of the complexes formed is pyridoxamine b H 2 pyr 2 en b H 2 pyr 2 an. Pyridoxal and pyridoxamine are forms of Vitamin B 6 and are non-toxic metabolites and this work promoted the start of many other studies involving pyridoxal Schiff base (pyr 2 en) and reduced Schiff base derivatives (pyr 2 an) by several groups including ours [155][156][157][158][159].…”
Section: Metal Ion-salen Complexesmentioning
confidence: 98%
“…[154] were published, either for the preparation and use of vanadium complexes or of other metal ions. As mentioned Schiff bases and reduced Schiff bases derived from pyridoxal have the advantage of being more compatible with solvents containing water, thus they were proposed either as ligands for the preparation of complexes with potential pharmaceutical use, or for homogeneous or supported catalytic systems to be used with water containing solvents [155][156][157][158][159].…”
Section: Metal Ion-salen Complexesmentioning
confidence: 99%
“…Schiff bases and their biologically active complexes have been often used as chelating ligands in the coordination chemistry of transition metals as radiopharmaceuticals for cancer targeting, agrochemicals, as model systems for biological macromolecules, as catalysts and as dioxygen carriers [4][5][6][7]. In recent years, metal complexes of Schiff bases have attracted dramatically attention due to their versatile biological activity, such as antifungal, antibacterial and antitumor [8][9][10]. It has been shown that the Schiff base complexes derived from salicylaldehyde and its derivatives with primary amines, bearing the N 2 O, N 2 S, NO 2 or NSO donor sets, have interesting biological activity [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%